2008
DOI: 10.1270/jsbbs.58.419
|View full text |Cite
|
Sign up to set email alerts
|

QTL detection for stickiness of cooked rice using recombinant inbred lines derived from crosses between japonica rice cultivars

Abstract: To establish a marker-assisted selection system for the eating quality of cooked rice, we performed quantitative trait locus (QTL) analysis using 188 recombinant inbred lines (RILs) derived from crosses of two japonica cultivars, 'Sakihikari' and 'Nipponbare'. The former has excellent eating quality with strong stickiness whereas the latter is less sticky. We evaluated the stickiness of cooked rice using a sensory test, as well as amylose content (AC), amylographic characteristics (AM), and days-to-heading of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 20 publications
(28 reference statements)
3
30
0
Order By: Relevance
“…Three QTLs, qADV6, qAC6.1 and qGCR6 mapped to the terminal region of the short arm of chromosome 6, corresponding to the wx locus (Harushima et al, 1998;Tan et al, 1999;Wan et al, 2004). This region includes important genes for good eating quality as revealed by several previous studies which have identified QTLs for eating quality near this region (Bao et al, 2000;Kobayashi and Tomita, 2008;Li et al, 2003;Suh et al, 2004;Takeuchi et al, 2007;Tanaka et al, 2006;Wada et al, 2006;Wan et al, 2004). In addition, there are several starch synthase-related genes on the short arm of chromosome 6, including waxy (Juliano, 1985;Sano, 1984), starch synthase I (Baba et al, 1993;Tanaka et al, 1995), and starch synthase IIa (Umemoto et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Three QTLs, qADV6, qAC6.1 and qGCR6 mapped to the terminal region of the short arm of chromosome 6, corresponding to the wx locus (Harushima et al, 1998;Tan et al, 1999;Wan et al, 2004). This region includes important genes for good eating quality as revealed by several previous studies which have identified QTLs for eating quality near this region (Bao et al, 2000;Kobayashi and Tomita, 2008;Li et al, 2003;Suh et al, 2004;Takeuchi et al, 2007;Tanaka et al, 2006;Wada et al, 2006;Wan et al, 2004). In addition, there are several starch synthase-related genes on the short arm of chromosome 6, including waxy (Juliano, 1985;Sano, 1984), starch synthase I (Baba et al, 1993;Tanaka et al, 1995), and starch synthase IIa (Umemoto et al, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…However, this trait is usually evaluated using a sensory test and needs to be done in advanced breeding generations (F 6 or later), which is both time consuming and labor intensive. Other selection methods, using as the measurement of physicochemical properties such as the ADV, AC, PC and gel consistency, have been used to evaluate eating quality indirectly (Bao et al, 2000;Kobayashi and Tomita, 2008;Li et al, 2003;Tanaka et al, 2006;Wada et al, 2006). Several studies have identified QTLs for such physicochemical properties and also for the eating quality of cooked rice using indica/japonica cross populations (Bao et al, 2000;Li et al, 2003;Ogata et al, 1996;Otsuki et al, 1997;Takeuchi et al, 2007;Wan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study revealed that a QTL for heading date, qDTH3, was linked to qLTG3-1. Furthermore, QTLs for agronomically important traits, eating quality (Kobayashi et al 2008, Takeuchi et al 2008, Wada et al 2008) and pre-harvest sprouting resistance (Hori et al 2010), have been identified in this chromosomal region. For the manipulation of these traits, targeted recombination within this chromosomal region should be useful for creating novel genotypes, which may provide novel advantages for adaptation for local environmental conditions.…”
Section: Discussionmentioning
confidence: 99%